In-situ friction monitoring of self-mated CVD diamond coatings using acoustic emission - Abreu, C. S. (2006)
In-situ measurements of acoustic emission (AE) in self-mated tribological pairs of CVD diamond coated silicon nitride (Si3N4) were made with the purpose of investigating the relationship between AE signal and friction events. A good correlation is found between the energy dissipation/emission processes, therefore enabling the possibility of monitoring the different friction regimes occurring during the sliding contact of microcrystalline diamond (MCD) coatings. Deposition of MCD on flat and ball-shaped Si3N4 samples was accomplished using microwave plasma assisted chemical vapour deposition (MPCVD) with H2/CH4 gas mixtures. The friction behaviour of self-mated MCD coatings was assessed using a reciprocating ball-on-flat geometry. The tests were run in ambient atmosphere without lubrication, the frequency (1Hz) and stroke (6mm) were kept constant while the applied normal load varied in the range 10-80N. The microstructure, surface topography and roughness of the MCD coatings were characterised by SEM and AFM techniques. The diamond quality was assessed from micro-Raman spectroscopy. The friction evolution was characterised by a short running-in period where the main feature is a sharp peak reaching values as high as approximately 0.6 followed by a steady-state regime with very low values in the range 0.03-0.04.